Manipulation of chondrogenic progenitor cells from late stages of osteoarthritis for cartilage repair - Schminke, B; Muhammad, H; Cingöz, G; Bode, C; Heyde, V; Miosge, N (AO Research Institute Davos, 2014)
INTRODUCTION: Regeneration of diseased hyaline cartilage continues to be a great challenge, mainly due to degeneration, caused either by major injury or by age-related processes. This usually overextends the tissue’s self-renewal capacity.